Toward Cooperative Collection Development in the Illinois Library and Information Network - Illinois State Library, Springfield; Illinois State Library, Springfield ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1977)
Findings and recommendations are reported by three subcommittees charged with determining the unmet needs of the Illinois Library and Information Network (ILLINET) and establishing a set of priorities that must be completed before the needs can be met. The report also addresses the responsibilities of cooperating libraries at all levels within the network, the role of the Research and Reference Centers, and the obligations of the state in supporting full library service to all users. Reports of each subcommittee are given in separate sections--Resource Identification, Access, and Responsibilities at All Levels, followed by the enumeration and discussion of specific recommendations. Major recommendations include: (1) all participating libraries in ILLINET should adopt and foster"user oriented acquisitions" as their collection development philosophy; (2) the state library should sponsor a statewide in-depth survey to determine unmet needs, examine subject strengths and from these examinations, specify system subject collection responsibilities; (3) ILLINET should study the feasibility of establishing a strategically located storage center (or centers) for little used or last copy materials; and (4) ILLINET should move toward conversion to machine readable form of the bibliographic holdings records of cooperating libraries. Appendices include cost estimates for a directory of libraries and information centers in the Chicago Metropolitan Area, description of the nominal group technique used to determine need priorities; and a report of the Illinois State Library Task Force on Non-Print Materials. (JPF)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Information Networks; Library Cooperation; Library Networks; Library Planning; Library Services; Needs Assessment; Statewide Planning; Illinois Library and Information Network; Reports, Research